KIDS CORNER SEBAGAI PROGRAM REVITALISASI ISTANA RAJA SERUWAY - Teuku Junaidi; Mufti Riyani; Ramazan (Global Science Society, 2020)
This community service is an implementation of the scientific field which is intended to revitalize the King Seruway Palace or commonly called the Aceh Tamiang Seruway Palace. Management carried out by the royal descent resulted in the Seruway Palace, now it is not functioning properly. The real step that can be done is to carry out a promotional program with a strategic target audience. The service program that was prepared involved early childhood students as the main target. The museum program was carried out after the dedication team was able to identify and repair the museum's activities such as the documentation, recording and layout of the museum collection. The next step taken is to develop a design with a design and design in accordance with the results of the assessment of the needs in the field. The resulting Kids Corner is an effort to provide space and activities for young people in Seruway Palace with designs and activities that can be carried out in them such as coloring, arranging puzlle with Seruway Palace theme and other activities with other educational games.